Improving the thermostability of feruloyl esterase by DNA shuffling and site-directed mutagenesis. Issue 11 (November 2015) - Li, Jing-Jing; Pei, Xiao-Qiong; Zhang, Shuai-Bing; Wu, Zhong-Liu
Graphical abstract: Highlights: A DNA shuffling library was constructed from four feruloyl esterases. Chimeras with enhanced thermal stability were identified. Half-life of the best chimera increased to 22-fold of the most stable parental FAE. Release of ferulic acid increases to 3.6–12.8-fold using the best chimera. Abstract: Feruloyl esterases (FAE) with high thermostability are greatly desired for efficient and economical industrial processes. A DNA shuffling strategy was applied to generate a chimeric library from four homologous FAEs originated from fungi. Chimeras with enhanced thermal stability compared to the parental FAEs were identified, which contained segments from 3 or 4 of the parental enzymes. After further incorporation of 2–4 additional beneficial mutations, the half-lives of inactivation of the chimeras at 65 °C were increased by up to 22 fold when compared to the most stable parental FAE. As a result, the release of ferulic acid from steam-exploded corn stalk using the best chimera was enhanced by 12.8-fold when compared to the best parental FAE.